Forensic and Toxicological Evaluation of High-Purity α-PVP (Flakka): Analytical and Structural Characterization of a Potent Synthetic Cathinone - Alizadeh Raef, Nima; Paknahad , Somayeh; Ghalari , Mohsen; Karimi Kashani , Mahdi; Gholipour , Maryam; Malmir , Arian; Visteh, Yasaman; Motahari , Zeynab; Mahdian, Tina; Sadeghi, Hani (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: α-Pyrrolidinovalerophenone is a potent synthetic cathinone, also known as “Flakka,” that has been associated with severe neuropsychiatric and cardiovascular toxicity. With its emergence worldwide, detailed analytical characterizations of high-purity α-PVP remain limited. In this study, the synthesis of α-PVP was performed under controlled laboratory conditions, followed by transformation to its hydrochloride salt and its further purification to an analytical-grade quality. Methods: Confirmation of the chemical structure and purity was carried out by using Fourier-transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (¹H NMR), and mass spectrometry. Results: The FTIR spectrum showed characteristic absorption bands at 3568–3478 cm⁻¹ (N–H stretching), 3091–2998 cm⁻¹ (C–H stretching), 1601 cm⁻¹ (aromatic C=C), and 1530 cm⁻¹ (C=O–N), confirming the pyrrolidinophenone framework. The ¹H NMR (400 MHz, CDCl₃) showed signals at δ 7.27–8.17 (m, Ar–H), 3.92 (t, N–CH₂), 2.57–2.74 (m, CH₂–N), 1.92–1.73 (m, CH₂), and 1.27–0.87 (t, CH₃), consistent with α-PVP. The base peak observed in the mass spectrum corresponded to m/z 126, for the pyrrolidine fragment. Analytical validation proved that purity was higher than 98%, with acceptable precision and linearity within forensic analytical limits. Conclusion: The findings pointed out structural determinants, notably the β-keto and pyrrolidine groups of α-PVP underlying dopaminergic overstimulation and sympathomimetic toxicity, respectively. The present work provides an extended analytical and toxicological reference for forensic laboratories for the distinguishing of authentic α-PVP from street analogues and for standardization in synthetic cathinone identification.